LITERARY TRANSLATION IS AN INTEGRAL PART OF UZBEK CULTURE AND FINE LITERATURE (Conference Zone, 2022)
This article is devoted to the translation of the first Uzbek works into Russian. In addition, the article provides information about the title of the translated work, the time of writing, the reason for the translation, the translators who translated.